2020
DOI: 10.1007/s10924-020-01899-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Presence and Possible Migration from Microplastics of Phthalic Acid Esters and Polycyclic Aromatic Hydrocarbons

Abstract: The work detailed here examined the presence and possibility of leaching of phthalic acid esters (PAEs) and polycyclic aromatic hydrocarbons (PAHs) from various products in everyday use. Due to the complicated matrix, which is plastic, extraction parameters should be selected separately each time. The properties of both the extractant and the material selected for testing should also be taken into account, which is very difficult in practice. In addition, when designing new methods, it is particularly importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The emission of methane and carbon dioxide from the decomposition of microplastics in the water environment was analyzed for three types of plastics, polyvinyl chloride (PVC), polypropylene (PP), and rubber (Table 2). Two types of polyvinyl chloride materials with low plasticizer content (gasket) and high plasticizer content (foil) were analyzed [27]. Polypropylene gloves were for everyday use, while rubber tires were used as car tires.…”
Section: Reagents and Materialsmentioning
confidence: 99%
“…The emission of methane and carbon dioxide from the decomposition of microplastics in the water environment was analyzed for three types of plastics, polyvinyl chloride (PVC), polypropylene (PP), and rubber (Table 2). Two types of polyvinyl chloride materials with low plasticizer content (gasket) and high plasticizer content (foil) were analyzed [27]. Polypropylene gloves were for everyday use, while rubber tires were used as car tires.…”
Section: Reagents and Materialsmentioning
confidence: 99%
“…After acetone extraction, the concentration of acenaphtylene, phenanthrene, fluoranthene and pyrene in PVC was 14.30, 2.64, 10.68 and 55.54 mg kg −1 , respectively; the concentration of anthracene, phenanthrene, fluoranthene and pyrene in rubber was 11.64, 5.63, 13.30 and 28.38 mg kg −1 , respectively. In comparison with PAH concentration determined in thermal-stabilized raw biomass, which showed the highest PAH content among the whole sample set (Table 1), the PAH content found in PVC and rubber [23] was almost 3 orders of magnitude higher, with the only exception of phenantrene concentration, which was higher in PHA samples (8.3 mg kg −1 ).…”
Section: Pah Contamination In Pha Samplesmentioning
confidence: 90%
“…Although there is no data availability in the literature regarding PAH determination in biobased plastics specially derived from waste, it is possible to compare the present results with a very recent study conducted on traditional plastics. Kida et al [23] determined the presence of PAHs in plastics (including polyvinyl chloride, PVC) and rubbers debris of different items, for example, PVC gaskets and rubber tyres. After acetone extraction, the concentration of acenaphtylene, phenanthrene, fluoranthene and pyrene in PVC was 14.30, 2.64, 10.68 and 55.54 mg kg −1 , respectively; the concentration of anthracene, phenanthrene, fluoranthene and pyrene in rubber was 11.64, 5.63, 13.30 and 28.38 mg kg −1 , respectively.…”
Section: Pah Contamination In Pha Samplesmentioning
confidence: 99%
“…Most PAEs in the air emerge from the production and incineration of plastic products, spraying of coatings, and volatilization of plasticizers in agricultural plastic films; these PAEs have been detected in the atmosphere worldwide [ 14 ]. Although the natural complete degradation of plastic is difficult, it can be decomposed into microplastics through processes including sun exposure, weathering, and abrasion, which leads to several adverse effects, such as PAE accumulation and enrichment in organisms through food chains, which endangers organism health and the natural environment [ 15 ]. Dubaish et al [ 16 ] reported the frequent appearance of suspended microplastics and black carbon particles in the coastal waters of the southern North Sea.…”
Section: Introductionmentioning
confidence: 99%